Mg²⁺-modified corncob biochar and natural zeolite significantly enhanced simultaneous N and P recovery from livestock wastewater - Yu Jin; Haifeng Wu; Shuai Huo; Siyu Chen; Lili Shen; Hongjie Di; Lianfeng Du; Peng Li (PLoS ONE, 2025)
Livestock and poultry farming effluents (LPFE) have become a significant source of pollution in the agricultural water environment, with nitrogen (N) and phosphorus (P) being the major pollutants. The use of inexpensive Mg2+ -modified materials as crystallization carriers can enhance the struvite crystallization and precipitation reaction, enabling efficient recovery of N and P nutrients from LPFE. In this study, Mg2+ -modified corncob biochar (CCBC-Mg) and Mg2+ -modified natural zeolite (NZ-Mg) were assessed for their simultaneous recovery of N and P from LPFE. BET, SEM-EDS, FTIR, XRD and adsorption isotherm and adsorption kinetics modelling were used to study the N and P adsorption properties and mechanisms. The results showed that Mg2+ modification significantly enhanced the simultaneous ammonia nitrogen (AN) and total phosphorus (TP) recovery of the two materials. After modification, corncob biochar (CCBC-Mg) showed the best P recovery performance, while natural zeolite (NZ-Mg) showed the best AN recovery, with adsorption quantities reaching 116.99 mg/g and 47.50 mg/g, respectively. The findings demonstrated that the adsorption processes for both AN and phosphate across all materials adhered to the pseudo-second-order kinetic model and Langmuir isotherm, collectively indicating that monolayer adsorption governed by chemical interactions was the predominant mechanism. CCBC and NZ mainly adsorbed AN and TP by electrostatic attraction and ion exchange, whereas CCBC-Mg and NZ-Mg, mainly relied on struvite precipitation on the material surface. The Mg2+ - modification increased the solution pH and formed Mg-P precipitates on the material surface, providing a favourable alkaline environment and nucleation conditions for the struvite reaction, thereby promoting the simultaneous recovery of AN and TP by the materials. This study could provide a theoretical basis for the design of struvite carrier for the simultaneous recovery of AN and TP from LPFE by the struvite precipitation method, and promote the application of this process in livestock and poultry farming effluent treatments.